Biorreator osmótico com membranas híbrido como alternativa para tratamento de efluente de refinaria de petróleo - Priscila Barbosa Moser (2021)
The increasing demand for water and related high generation of oil refineries effluents, because of products with high degree of purity, which favors fuel potential, combined with restrictive environmental laws, grounded on sustainability concerns. It emerges as an attempt to reduce impact on catchment areas, promote development, technological improvements while integrating of processes that enable industrial water reuse in technology parks. Moreover, the refining effluent characteristic, consisting of aromatic hydrocarbons, oil and greases, phenolic and sulfur substances, in addition to recalcitrant compounds, corroborate the viable use of such methods in the industrial sector. Embedded in this context, osmotic bioreactors (BRMO), i.e., the integration of the activated sludge process with the membrane separation, direct osmosis (OD) process and its ramifications, hybrid systems such as BRMO + UF, have been used as novel sustainable technologies, contributing to energy costs savings, removal of difficult degradation compounds, as well enabling quality water reuse for application in cooling towers and boilers. As an important Osmotic process variable, saline / osmotic solutions integrate the driving forces of this process, whose integration and dynamics in the reactor contribute to system improvement and, consequently, to the quality of the treated effluent. Moreover, to be highlighted are the salinity effect, due to the diffusing effect of the solute of this solution, and related implications to the performance of the bioreactor. The results obtained so far were based on the effect of two different osmotic solutions (OS) on the biodegradation of recalcitrant compounds in a hybrid ultrafiltration osmotic membrane bioreactor (BRM+UF) UF acting as a system purge, contributed to the stabilization of the saline effect. The operation was carried out continuously (505 days), treating a real oil refinery effluent. When sodium chloride (NaCl) was used as SO, the permeate flow from direct osmosis (FO) was 1.07 ± 0.32 (L/m2·h), while for sodium acetate (CH3COONa) the flow permeate was slightly lower (0.60 ± 0.15 L/m2·h). Simulations showed that the accumulation of salinity in a conventional BRMO would be 10x and 5x times greater for NaCl and CH3COONa, respectively, compared to BRMO + UF. UF, however, was not able to alleviate the accumulation of recalcitrant compounds in the reactor when operated with NaCl, which led to a decline in the efficiency of the process. The use of CH3COONa as SO, in turn, favored microbiological activity and increased the biodegradation of recalcitrant compounds. Evaluations considering only the osmotic system, BRMO, when operated with magnesium chloride (MgCl2) as OS, presented the permeate with good physical- chemical quality, due to the increase in the time of retention of contaminants, and can be used even in applications that demand high operational quality. When compared to other bioreactors, there is greater degradation of recalcitrant compounds. Furthermore, the decrease in flow due to the increase in salinity, due to the reverse flow of magnesium, in addition to the dilution of OS, may favor the nitrification process. Finally, recovering the osmotic solution increases process operating rates, reducing costs, and promoting process sustainability.